92: Does The Prenatal Consultation for Preterm Labor Worry, Reassure Or Both?. Issue 6 (1st June 2014) - Gaucher, N; Nadeau, S; Barbier, A; Payot, A
Abstract: BACKGROUND: Recommendations encourage informing mothers at risk of preterm labor. OBJECTIVES: To evaluate whether prenatal consultations for preterm labor worry or reassure women at risk of preterm delivery. DESIGN/METHODS: This was a prospective survey of hospitalized women at risk of preterm delivery 26 to 32 weeks GA, who had met the neonatologist for prenatal consultation in the last 72 h. The tool was developed using data from a qualitative exploratory study; construct and content validity were accounted for through several validation phases. A single-center study was conducted in 2008, leading to a multicenter trial in three tertiary care university hospitals (Apr. 2012–Sept. 2013). Variables were analyzed using Chi2 tests; qualitative data was transcribed and categorized to identify emerging themes. RESULTS: A total of 229 of 334 surveys were returned (67.2%). Participants' experiences were positive (89.9%). 23.3% were worried by the consultation, while 87.2% were reassured by it – reasons provided in table. Longer consultations were associated with reassurance (P<0.001). 66.1% of women's perception of prematurity changed after the consultation. Of these, 51.3% changed for the better: the facts that the complications of prematurity and survival rates were better than anticipated, that feeling informed was a reassurance, and that a sense of competence and trust were instilled by neonatologists all contributed to this improvement. 6.3% changed for the worse due to prematurity's complications being greater than expected. 33.9% of women's perceptions – mostly negative or worried – remained unchanged; many reported already knowing about prematurity, but felt better informed by the meeting. GA (below vs. over 30 wks GA) was associated with a change in perception on prematurity (P<0.05), but not with worrisome or reassuring consultations. CONCLUSIONS: To be reassuring, neonatologists should strive to establish a trusting relationship with mothers, in which realistic, clear, but optimistic, information is offered. Most women's outlooks on prematurity can improve through such a process, especially at an earlier GA.